PENYELESAIAN SENGKETA TANAH KARENA PERBUATAN MELAWAN HUKUM (Studi Putusan Pengadilan Negeri Yogyakarta Nomor 101/Pdt.G/2019/PN Yyk - Anggun Puji Lestari; Subekti; Nur Handayati; Marwiyah, Siti (Jurnal Hukum Ius Publicum, 2024)
Land disputes are conflicts between two or more people who have the same property interest in the status of land object rights between one or several land objects result in certain legal consequences for the parties. An unlawful act is the consequences of an act that is contrary to the law are also regulated by law, even though the consequences were not intended by the person committing the act. Factors causing land dispute lawsuits due to unlawful acts. Study Yogyakarta District Court Decision Number 101/Pdt.G/2019/PN Yyk, there are 3 factors namely: the main factor is that the Defendant is proven to have committed an unlawful act, the second factor The plaintiff suffered material and immaterial losses, and the final factor is existence the dispute is whether the object of the dispute belongs to Moehamad Djani (the Plaintiff's parent) or owned by Slamet Partosudarmo. Consideration of the panel of judges in action lawsuit cases against the law in land disputes Study Decision Number 101/Pdt.G/2029/PN Yyk is The letter from the Plaintiff cannot yet be used as a reference for the Panel of Judges to examine the material lawsuit because there is still a lack of parties in this case.